2015
DOI: 10.1177/1057567715580985
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Job Variables With Job Involvement, Job Satisfaction, and Organizational Commitment Among Indian Police Officers

Abstract: Past empirical research has indicated that workplace factors affect the work attitudes of police officers. Police officers ( N = 827) were surveyed in two districts (Sonipat and Rohtak) in the State of Haryana in the Republic of India. Ordinary least squares regression analysis was used to test the effects of job variables (i.e., job autonomy, job variety, training, and supervision) on job attitudes (i.e., job involvement, job satisfaction, and organizational commitment). Results indicate that variety, trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 47 publications
5
73
0
1
Order By: Relevance
“…Robie et al (1998) have attributed the impact of rank on job satisfaction to the power distance among the ranks and recommend that the reduction of power distance would reduce the difference in job satisfaction. Research in India has reported mixed findings with Lambert et al (2015) finding no impact of rank on job satisfaction and Kumar (2017) reporting a significant relationship between the variables.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Robie et al (1998) have attributed the impact of rank on job satisfaction to the power distance among the ranks and recommend that the reduction of power distance would reduce the difference in job satisfaction. Research in India has reported mixed findings with Lambert et al (2015) finding no impact of rank on job satisfaction and Kumar (2017) reporting a significant relationship between the variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Female officers experience higher levels of stress at the workplace (He, Zhao, and Archbold, 2002) due to the organizational culture, characteristics of the work environment, and demands from family. Surprisingly, most studies have reported that gender does not have a significant impact on job satisfaction (Johnson, 2012;Lambert, Qureshi, Hogan, Klahm, Smith, and Frank, 2015;Miller et al, 2009;Zhao et al, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the JD-R model and COR theory, mediation and adjustment analyses can be used to determine the relationships between these variables, thus making it a worthy topic for further study. In addition, existing research has mainly focused on police officers in Western nations, particularly the United States (Lambert et al, 2015). Thus, it is necessary to perform research involving police officers from an array of countries, including non-Western nations.…”
Section: Regulatory Emotional Self-efficacy As a Moderatormentioning
confidence: 99%
“…Singkatnya, keterlibatan kerja karyawan merupakan intensitas psikologis yang membentuk pekerjaannya (Lambert et. al., 2015).…”
Section: Keterlibatan Kerjaunclassified